Biased MAIT TCR Usage Poised for Limited Antigen Diversity? - Souter, Michael N. T.; Eckle, Sidonia B. G. (Frontiers in Immunology, 2020)
Mucosal-associated invariant T (MAIT) cells are a subset of unconventional T cells that recognise the evolutionarily conserved major histocompatibility complex (MHC)-like antigen-presenting molecule known as MHC class I related protein 1 (MR1). Since their rise from obscurity in the early 1990s, the study of MAIT cells has grown substantially, accelerating our fundamental understanding of these cells and their possible roles in immunity. In the context of recent advances, we review here the relationship between MR1, antigen and TCR usage among MAIT and other MR1-restricted T cells and provide a speculative discussion.